HER: Humanities Entity Recognizer. Software. - BESHERO-BONDAR, ELISA (Renaissance & Reformation / Renaissance et Réforme)
The article reviews the "HER, or the Humanities Entity Recognizer" optimized for digital humanists who work with specialized text corpora composed in times and languages mostly unrepresented in corporate-driven, machine-learning algorithms.